Cell Wall Biosynthesis Genes Variability in Methicillin-Resistant Staphylococcus Aureus with Reduced Vancomycin Susceptibility - V. V. Gostev; O. S. Kalinogorskaya; O. A. Dmitrenko; S'. M. Yudin; A. V. Kudryavtseva; S. V. Sydorenko (Антибиотики и Химиотерапия)
The problem of formation and spread of S.aureus isolates with reduced sensitivity to vancomycin (Vancomycin intermediate S.aureus, VISA) limits the use of this antibiotic for the treatment of infections caused by MRSA. The formation of such a phenotype is complex and is associated with the accumulation of mutations in the genes involved in the biosynthesis of the cell wall. Genomic sequencing of seven isolates with different sensitivity to vancomycin and belonging to the same genetic line was carried out in the study: ST8 - t008 - SCCmec IVc. PAP analysis of isolates with reduced sensitivity to vancomycin did not reveal hVISA/VISA phenotypes, while PAP/AUC was 0.53-0.7. Comparison of 83% of the core parts of isolates’ genomes with MIC = 1 mg/ml and 2 mg/ml, as well as control genomes (NCBI GenBank) with known sensitivity, revealed different clustering, the isolates with MIC=2 mg/ml were localized in one cluster. Comparison of the nucleotide concatenate composed of 44 genes involved in the assembly of the cell wall also showed that the isolates were assembled into one cluster. Unique mutations were identified for isolates with MIC=2 mg/ml in murZ (T353A), rpoB (Y946C), and fdh2 (G446S). Thus, isolates with reduced sensitivity to vancomycin did not have the hVISA or VISA phenotype. However, the identified mutations in the «key» genes of peptidoglycan biosynthesis may indicate the initial stage of selection of resistance to vancomycin with the formation of pre-hVISA.